Characterization of Myf6 and association with growth traits in swimming crab (Portunus trituberculatus) - Baohua Duan; Weibiao Liu; Chen Zhang; Tongxu Kang; Haifu Wan; Shumei Mu; Yueqiang Guan; Zejian Li; Yang Tian; Yuqin Ren; Xianjiang Kang (BMC Genomics)
Abstract Background Myogenic factor 6 (Myf6) plays an important role in muscle growth and differentiation. In aquatic animals and livestock, Myf6 contributes to improving meat quality and strengthening the accumulation of muscle flavor substances. However, studies on Myf6 gene polymorphisms in crustaceans have not been reported. Results In the current study, we characterized the Myf6 gene for Portunus trituberculatus to better understand its biological function. The full-length cDNA of Myf6 was 4,101 bp, with a 915 bp open reading frame encoding 304 amino acids. In addition, Myf6 included a conservative bHLH domain. Homology analysis showed that Myf6 shared the highest identity with Penaeus vannamei. Expression pattern analysis of Myf6 in fast- and slow-growing groups revealed that the expression level of the latter was significantly higher than that of the former (P < 0.05). qPCR studies revealed that Myf6 was expressed in various tissues with the highest level in muscle. Nineteen single nucleotide polymorphisms (SNPs) of Myf6 were identified and five of them were significantly associated with growth-related traits of P. trituberculatus (P < 0.05), including full carapace width, carapace length, body height, and body weight. The AG and GG genotypes of g.1,187,834 A > G exhibited superior growth-related traits than the AA genotype. In the combined genotypes of g.1,187,324 C > T and g.1,187,834 A > G, the average body weight of diplotype D5 (CT-GG) was higher than that of diplotype D1 (CC-AA), D2 (CC-AG), and D3 (CC-GG) in a cultivated population. A haploblock was generated by three significant SNPs (g.1187834 A > G, g.1188616 A > G, and g.1189024 C > A), containing four haplotypes (AAA, AAC, AGC, and GGC), among which GGC haplotype exhibited superior growth traits (full carapace width and body weight) than the AAA haplotype. Conclusions To our knowledge, this is the first report on Myf6 in crustaceans. The results of this study would contribute to elucidating multiple functions of the Myf6 gene in crustaceans and exploring the potential as a candidate gene in selective breeding programs of P. trituberculatus.